Psychological Contract Sebagai Alternatif dalam Meninjau Pemenuhan Harapan Akademik di Perguruan Tinggi - rezki ashriyana sulistiobudi (PSIKODIMENSIA, 2017)
Abstract Higher education, as an institution that generates the nation's next future leader, is no longer burdened with merely providing knowledge alone. Human resource competitiveness was being one of higher education responsibility to complete, to achieve a great quality of their graduates. Hope that emerged from the students on the fulfillment of obligations towards their university becomes something that can not be separated from the quality of the graduates. Psychological contract as a concept that can explain it, has not been widely studied in a higher education setting especially in Indonesia. The number of measuring instruments has its version on some theoretical models raises curiosity as to what is actually appropriate. Through the method of literature review, it was carried out a critical discussion of the components in the measurement of psychological contract at higher education institutions. The exposure in understanding the dynamics of inter-dimensional and determine the appropriate model based on the characteristics of each academic institution. At least, measurement of psychological contract used in higher education setting should be both of promissory (transactional) and non-promissory (relational) dimension. Surely, it always needs to adjust to the conditions and situations relevantly in each institution. Therefore, it would be possible to bring various indicators in each of dimension.